Impulse Buying in Mall Settings: An Ethnographic Study of Makassar Shoppers - Riu, Isma Azis (Malaqbi Publisher, 2025)
This ethnographic study examines the triggers and patterns of impulse buying behavior among shoppers in three major shopping malls in Makassar, Indonesia: Panakkukang Mall, Nipah Mall, and Global Trade Center (GTC). Using a qualitative methodology combining participant observation and semi-structured interviews with 18 participants over six months, this research identifies key environmental, social, and promotional factors that influence unplanned purchasing decisions. The findings reveal that store atmospherics—including bright lighting, upbeat music, and scent marketing—significantly correlate with impulse buying behavior, with aromatic influences generating 2.3 times more unplanned purchases. Social dynamics emerged as equally influential, with shoppers in groups demonstrating 67% higher impulse buying rates compared to solitary shoppers, while peer validation and family presence, particularly children, substantially affected purchasing decisions. Promotional strategies, especially flash sales and buy-one-get-one offers, proved highly effective, with 91% of promotional announcements generating immediate purchasing responses. Demographic analysis indicated that female shoppers (67% of observed impulse buyers), individuals aged 25-40 years (54% of instances), and middle-income earners (3-8 million IDR monthly) exhibited the highest frequency of impulse purchasing behaviors. Temporal patterns showed peak activity during weekend afternoons and weekday evenings, with seasonal promotional periods increasing impulse buying rates by 45%. The study contributes to consumer behavior literature by providing culturally contextualized insights into impulse buying mechanisms in emerging markets, while proposing practical spatial design adjustments for mall environments that balance commercial viability with consumer welfare. These findings have implications for retail practitioners, urban planners, and consumers seeking to understand and manage unplanned spending behaviors in contemporary Indonesian shopping contexts.